Sea-level fluctuations and coastal evolution in the state of Rio de Janeiro, southeastern Brazil - CASTRO,JOÃO WAGNER A. (2014)
The present paper aims to investigate the relative sea-level and the coastal evolution during the Holocene in the Rio de Janeiro coastline, based on geological and biological indicators. Using topographic survey, excavation and coring, and 14C dating of these coastal deposits and beachrocks outcrops, we have reconstructed a sea-level curve for the Holocene. For the first time on the Brazilian coast it was identified a negative record of relative sea-level during Late Pleistocene and Early Holocene transition. After the transition, a relatively rapid increase of sea-level began. At approximately at 8500 cal yr BP, the sea-level was 0.5 m below the current level, was overtaken for the first time in the Holocene, at approximately 7500 cal yr BP. The maximum level of +2.5 m was reached between 4770 and 4490 cal yr BP. At the point of maximum transgression, the sea-level began a general behavior of lowering until the present. These results confirm other data already obtained elsewhere along the Atlantic coast of South America. The results of this study are consistent with previous researches and they help to refine the Holocene sea-level record along the Brazilian coast.